Commuting matrices

 

This post arose from an attempt to solve a question in this past Waterloo pure mathematics PhD comprehensive exam.

Let k be an algebraically closed field. Let \mathcal M_n(k) denote the set of all n\times n matrices with entries in k. Let

\displaystyle J_\lambda:=\left(\begin{matrix}\lambda & 1 & \cdots & 0\\ 0 & \lambda & \cdots & 0\\\vdots & \vdots & \ddots & \vdots\\ 0 & 0 & \cdots & \lambda\end{matrix}\right)\in\mathcal M_n(k)

be a Jordan block. Let e_1,\dots,e_n be the standard basis vectors, i.e. the j-th component of e_i is \delta_{ij}. Note the action of J_0 on the basis vectors: J_0e_i=e_{i-1} for each i (where we take e_0=0).

Suppose P\in\mathcal M_n(k) commutes with J_\lambda. Then

Pe_{i-1}=PJ_0e_i=P(J_\lambda-\lambda I)e_i=(J_\lambda-\lambda I)Pe_i=J_0Pe_i

i.e. if P_i:=Pe_i is the i-th column of P, then P_{i-1}=J_0P_i for each i. Thus

P=(P_1\mid\cdots\mid P_n)=(J_0^{n-1}P_n\mid\cdots\mid P_n)=(J_0^{n-1}\mid\cdots\mid I)P_n

i.e. if P_n=(a_1,\dots,a_n)^T, then P=a_1J_0^{n-1}+\cdots+a_nI, a polynomial in J_0. Further, since J_0=J_\lambda-\lambda I, it follows that P is a polynomial in J_\lambda. So we deduce:

Fact 1. P commutes with J_\lambda iff P is a polynomial in J_0.

Fact 2. P commutes with J_\lambda iff P is a polynomial in J_\lambda.

If we denote

\mathcal C(A):=\{B\in\mathcal M_n(k): AB=BA\}

for A\in\mathcal M_n(k), then we’ve just shown

\begin{aligned}\mathcal C(J_\lambda)&=\{f(J_\lambda):f\in k[X]\}\\ &=\{f(J_0):f\in k[X]\}\\ &=\mathcal C(J_0)\end{aligned}

Now let A\in\mathcal M_n(k) have minimal and characteristic polynomial (X-\lambda)^n. This means the Jordan normal form of A is J_\lambda. So there exists an invertible matrix M such that A=MJ_\lambda M^{-1}. Thus

\begin{aligned}\mathcal C(A)&=\{P\in\mathcal M_n(k): PA=AP\}\\ &=\{P\in\mathcal M_n(k):PMJ_\lambda M^{-1}=MJ_\lambda M^{-1}P\}\\ &=\{P\in\mathcal M_n(k): M^{-1}PMJ_\lambda=J_\lambda M^{-1}PM\}\\ &=\{P\in\mathcal M_n(k): M^{-1}PM=f(J_\lambda)\text{ for some }f\in k[X]\}\\ &=\{P\in\mathcal M_n(k): P=Mf(J_\lambda)M^{-1}\text{ for some }f\in k[X]\}\\ &=\{P\in\mathcal M_n(k): P=f(MJ_\lambda M^{-1})\text{ for some }f\in k[X]\}\\ &=\{P\in\mathcal M_n(k): P=f(A)\text{ for some }f\in k[X]\}\\ &=\{f(A): f\in k[X]\}\end{aligned}

Thus

Fact 3. P commutes with A iff P is a polynomial in A.

Advertisements

Leave a comment

Filed under Linear algebra

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s